Pemberdayaan Masyarakat Ekonomi Lokal melalui Strategi Manajemen Usaha Ternak Sapi di Desa Padang Baru: Empowerment of Local Economic Community through Cattle Farming Business Management Strategy in Padang Baru Village - Guspian, Iza; Wahyudin, Nanang; Wibawa, Dian Prihardini; Noviyanti, Indah; Saputra, Darman; Aryansyah, Ary Fakturrachman; Kusumah, Echo Perdana; Sumar, Sumar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Cattle farming in Padang Baru Village plays a vital role in empowering the local economy, especially in the livestock sector which is one of the sectors with the largest population on Bangka Island. However, the limitations of the local community in being able to utilize the potential of resources have caused the progress of cattle sales to be less than optimal. The purpose of this Community Service is to improve the knowledge and skills of cattle farming entrepreneurs through business management strategies, namely marketing strategies and digital content design. The implementation of activities uses the method of socialization and direct practice to cattle technology actors, cattle businesses, related stakeholders, and local community leaders. The results of the community service showed that participants were enthusiastic about asking questions and gaining new knowledge on how to implement programs to market cattle and provide a touch of digital product content that attracts consumer interest. It is hoped that the community empowerment approach in the cattle business management strategy, will create a multiplication effect in the local economy and maximum economic growth.